Термодинаміка формування рідких прошарків в композиційних матеріалах - Лiсовський, А. Ф.; Давиденко, С. А. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2019)
Composite materials consisting of refractory particles and a low-melting binder have been studied. In a composite body the process of the liquid outflow from a capillary into the body bulk have been described in terms of thermodynamics. An equation for the variation of the Helmholtz free energy of a microdispersed system during this process has been derived and the conditions, under which the liquid interlayers are either stable or unstable in the bulk of a composite body, have been established.